A multidonor class of highly glycan-dependent HIV-1 gp120-gp41 interface-targeting broadly neutralizing antibodies - Evan M. Cale; Chen-Hsiang Shen; Adam S. Olia; Nathan A. Radakovich; Reda Rawi; Yongping Yang; David R. Ambrozak; Anthony K. Bennici; Gwo-Yu Chuang; Emma D. Crooks; Jefferson I. Driscoll; Bob C. Lin; et al. (Cell Reports)
Summary: Antibodies that target the gp120-gp41 interface of the HIV-1 envelope (Env) trimer comprise a commonly elicited category of broadly neutralizing antibodies (bNAbs). Here, we isolate and characterize VRC44, a bNAb lineage with up to 52% neutralization breadth. The cryoelectron microscopy (cryo-EM) structure of antibody VRC44.01 in complex with the Env trimer reveals binding to the same gp120-gp41 interface site of vulnerability as antibody 35O22 from a different HIV-1-infected donor. In addition to having similar angles of approach and extensive contacts with glycans N88 and N625, VRC44 and 35O22 derive from the same IGHV1-18 gene and share convergent mutations, indicating these two antibodies to be members of the only known highly glycan-dependent multidonor class. Strikingly, both lineages achieved almost 100% neutralization breadth against virus strains displaying high-mannose glycans. The high breadth and reproducible elicitation of VRC44 and 35O22 lineages validate germline-based methods of immunogen design for targeting the HIV-1 gp120-gp41 interface.